Analisis Kontingensi pada Sistem Pemakaian Sendiri PLTU Ombilin - Yulisman Yulisman; Fiki Rahman (Universitas Batanghari Jambi, 2022)
The continuity of electrical energy requires an electric energy management with high efficiency and easy-to-obtain fuel. One of them is the Ombilin Steam Power Plant (PLTU) with a capacity of 2 x 100 MW. At ombilin power plant there is a system of its own use that is obtained from the generator when the plant is operating. In this study, contingency analysis was conducted on its own system simulated using ETAP 12.6 software. Contingency analysis is the study of the safety of an electric power system by conducting a power flow analysis of the impact of a number of contingency cases such as the release of one or more generators and the release of one of the tramsmission elements. With contingency analysis, an electric power system will be able to calculate the disruption that occurs for example in the use of a power plant unit, so that it can predict changes in system capacity and the remaining bus voltage whether it can still be burdened or has experienced overload conditions. In this study, a contingency analysis was conducted on the Ombilin PLTU's own usage system with 5 scenarios to see the results of voltage and performance index (IP) when contingencies occurred with 5 scenarios then ranked. Based on the results of 5 scenarios, the highest voltage obtained in scenario-3 is 6.18 kV with a performance index (IP) of 2.4915 and the lowest voltage in scenario-4 is 6.13 kV with a performance index (IP) of 3.1526.